TES DIAGNOSTIK UNTUK PROGRAM REMEDIAL PADA PEMBELAJARAN MATEMATIKA - SADONO SADONO (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2012)
The purpose of this research is to find out the impact level of providing diagnostic test with remedial test and the student’s previous knowledge initial capability to the learning achievement of Junior High School maths in Jakarta. The initial capability is divided into two. They are the low initial capability and the high initial capability. There are four hypotheses in that research. First, the student maths learning achievement provided diagnostic test with remedial test after the school hour is better than that of being provided diagnostic test with remedial along the school hour. Second, there is correlation between the student learning achievement provided diagnostic test and the student initial capability. Third, for the students with high initial capability, the maths learning achievement provided diagnostic test after school is better than of being provided with remedial test along the school hour. Fourth, the students with low initial capability. The maths learning achievement provided diagnostic test with remedial test after the school hour is better than that of being provided diagnostic test with remedial test along the school hour. The research data got was analyzed by using Analysis of Variance (ANAVA) two-way. Based on the method, if there are significant differences, the next test must be administrated. The hypothesis testing result showed that: (1) the learning achievement for the students provided diagnostic test with remedial test after the school hour was better than of students provided with remedial along the school hour, (2) relatively there was no significant correlation between the student learning achievement provided diagnostic test with remedial test and the student initial capability. The implication of the research result is that the remedial test provided by teachers can help student’s enhance the achievement of the targeted minimum completeness criteria of school grade for each subject.